Landscape archaeology in a contested space: Public engagement and outreach in the Xeros River valley in Cyprus - Vionis, Athanasios K.; Papantoniou, Giorgos; Savvides, Niki (Journal of Greek Archaeology, 2023)
This paper presents the activities carried out in the context of the public outreach framework of the Settled and Sacred Landscapes of Cyprus (SeSaLaC) and the Unlocking the Sacred Landscapes of Cyprus (UnSaLa-CY) projects of the Archaeological Research Unit of the University of Cyprus in a former conflict zone, the Xeros River valley (Larnaca district) in Cyprus. The public outreach initiatives were born out of the long-term aim of the projects to encourage public engagement and interaction of the present-day communities in the Xeros valley with the cultural heritage of the region.